Elementary school students' epistemic perspective and learning strategies in history. (2nd July 2020) - Ioannou, Kalia; Iordanou, Kalypso
ABSTRACT: The present study explores possible relations between students' epistemic perspective, learning strategies and text comprehension. In Study 1, 79 sixth graders completed paper-and-pencil instruments to measure their epistemic perspective and learning strategies. Students' epistemic perspective was assessed using a scenario-based instrument, the Livia Problem. Students were epistemically profiled as Absolutists, Multiplists and Evaluativists. Students' learning strategies were assessed through the Motivated Strategies for Learning Questionnaire (Pintrich & De Groot, 1990). In Study 2, 20 of the students who participated in Study 1 were individually interviewed to measure their learning strategies, where they were asked to read a text and think aloud. Results revealed that students who were profiled as Evaluativists showed greater self-efficacy, intrinsic value, use of cognitive strategies and self-regulation. In addition, students who were profiled as Evaluativists engaged in more effective learning strategies and exhibited better text comprehension compared to students who were profiled as Absolutists. In particular, students who exhibited an Evaluativist epistemic perspective engaged in the strategies of understanding vocabulary, summarising and underlying, while students who exhibited an Absolutist epistemic perspective engaged more in repeating information and quick reading. Our findings show that a mature epistemic perspective is associated with effective usage of learning strategies and text comprehension.